Increased isoprostane and prostaglandin are prominent in neurons in Alzheimer disease - Siedlak Sandra L; Capobianco Dae E; Hua Jing; Basu Samar; Smith Mark A; Casadesus Gemma; Zhu Xiongwei; Perry George (Molecular Neurodegeneration, 2007)
Abstract Background Inflammation and oxidative stress are both involved in the pathogenesis of Alzheimer disease and have been shown to be reciprocally linked. One group of molecules that have been directly associated with inflammation and the production of free radicals are the prostaglandin 13,14-dihydro 15-keto PGF2α and the isoprostane 8-iso-PGF2α. Results To further delineate the role of inflammatory and oxidative parameters in Alzheimer disease, in this study we evaluated the amount and localization of 13,14-dihydro 15-keto PGF2α and 8-iso-PGF2α in hippocampal post mortem tissue samples from age-matched Alzheimer disease and control patients. Our results demonstrate increased levels of 13,14-dihydro 15-keto PGF2α and 8-iso-PGF2α in the hippocampal pyramidal neurons of Alzheimer disease patients when compared to control patients. Conclusion These data not only support the shared mechanistic involvement of free radical damage and inflammation in Alzheimer disease, but also indicate that multiple pathogenic "hits" are likely necessary for both the development and propagation of Alzheimer disease.